Uranium [videorecording (DVD)] : twisting the dragon's tail - Fimeri, Wain (2015)
"Legends say there's a world beneath this one where a dragon lies sleeping. They say be careful how you wake the dragon. The year 2015 marks the 70th anniversary of the most profound change in the history of human enterprise on Earth: the unleashing of the elemental force within uranium, the explosion of an atomic bomb, the unleashing of the dragon. The story of uranium is part science, part history and all epic adventure. From its creation in an exploding star to its deployment in nuclear weapons, nuclear power, and nuclear medicine, Uranium, Twisting the Dragon's Tail is a journey across nine countries and more than a century of stories to discover the rock that made the modern world. Join physicist Dr. Derek Muller, creator of YouTube channel Veritasium as he travels to Ukraine, Japan, North America, Europe and Australia to find the untold story of the most dangerous, wondrous, and controversial rock on Earth"--Container.